1993
DOI: 10.1139/v93-085
|View full text |Cite
|
Sign up to set email alerts
|

1H nuclear magnetic resonance and molecular orbital studies of the internal rotational potential and electron delocalization in triphenylphosphine

Abstract: . Can. J. Chem. 71, 639 (1993). The 'H nuclear magnetic resonance spectral parameters are reported for triphenylphosphine as solutions in CS,/C6D12 and acetone-d6 at 300 K. 'The internal rotational potential opposing torsion about the P-C bond is computed by AM1 and STO-3G MO methods. The computed potentials are used to calculate the average shielding of the para protons caused by the diamagnetic anisotropies of the neighbouring phenyl groups. The results are used to estimate the degree of electron delocalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…To isolate these differential shifts from those caused by the diamagnetic anisotropy, AX, of the phenyl group in 1, the model in ref. 36 was applied. This model relates the shift cause by AX to (sin20), the expectation value of sin20, where 0 is the torsion angle about the csp3-csp2 bond in 1.…”
Section: The Chemical Shifs Of the Alkyl Protonsmentioning
confidence: 99%
“…To isolate these differential shifts from those caused by the diamagnetic anisotropy, AX, of the phenyl group in 1, the model in ref. 36 was applied. This model relates the shift cause by AX to (sin20), the expectation value of sin20, where 0 is the torsion angle about the csp3-csp2 bond in 1.…”
Section: The Chemical Shifs Of the Alkyl Protonsmentioning
confidence: 99%
“…13 Since the precise C 3 symmetry at the phosphorus site does not exist in the crystal lattice, 14 the question arises whether averaging of the perpendicular components results from large-amplitude motions of the phenyl rings. 15 A lowtemperature measurement, at 133 K, was performed, which showed that the shift anisotropy and span were essentially unchanged. The measured values for the individual shift tensor elements are given in Table 1 and are in good agreement with those reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…The shielding tensor of PPh 3 has been investigated previously, but only at room temperature, and an axially symmetric powder pattern was observed . Since the precise C 3 symmetry at the phosphorus site does not exist in the crystal lattice, the question arises whether averaging of the perpendicular components results from large-amplitude motions of the phenyl rings . A low-temperature measurement, at 133 K, was performed, which showed that the shift anisotropy and span were essentially unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…The barrier to internal rotation in benzaldehyde is calculated as 37.5 kJ/mol with the 6-31G* basis (18), rather highe? than, for example, the free energy of activation of 32.2(6) kJ/mol in solution (19)(20)(21).…”
Section: The Theoretical Conformational Propertiesmentioning
confidence: 99%